ChemInform Abstract: Half‐Metallicity in Pb2CoReO6 Double Perovskite and High Magnetic Ordering Temperature in Pb2CrReO6 Perovskite. Issue 35 (September 2015) - Retuerto, Maria; Li, Man‐Rong; Stephens, Peter W.; Sanchez‐Benitez, Javier; Deng, Xiaoyu; Kotliar, Gabriel; Croft, Mark C.; Ignatov, Alexander; Walker, David; Greenblatt, Martha
Abstract Pb2MReO6 (M: Co (I), Cr (II)) perovskites are prepared by hot pressing of stoichiometric amounts of PbO, Cr2O3 (CoO), Re, and ReO3 (Pt capsule in multianvil press, 1423 (I) and 1473 K (II), 8 GPa, 30 min).